2005
DOI: 10.1021/jf0511392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Stone Content on the Quality of Plum and Cherry Spirits Produced from Mash Fermentations with Commercial and Laboratory Yeast Strains

Abstract: To evaluate the influence of stone content on spirit quality from stone fruit, cherry and plum mashes were prepared and fermented with a commercial and a diploid laboratory yeast strain. Fermentation parameters such as sugar content and ethanol production were followed. Despite an initial lag phase in cherry spirits, both yeast strains performed similarly, as substantiated by the determination of specific flavor compounds, ethyl carbamate, and methanol in the mashes and after distillation. The spirits produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 17 publications
(18 reference statements)
6
36
0
Order By: Relevance
“…It means that one product of hydrolysis is desirable (consumers often desire the typical 'biter almond'), and the other be accompanied by detrimental inluences and health risks [58]. It is particularly important not to largely crush the stone during preparation of stone fruits mashes for the fermentation.…”
Section: Distillation -Innovative Applications and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that one product of hydrolysis is desirable (consumers often desire the typical 'biter almond'), and the other be accompanied by detrimental inluences and health risks [58]. It is particularly important not to largely crush the stone during preparation of stone fruits mashes for the fermentation.…”
Section: Distillation -Innovative Applications and Modelingmentioning
confidence: 99%
“…Another important item is that distiller should not be carried out distillation of fermented mash with stone in the pot. Investigation of Schehl et al [58] showed that the presence or absence of stones in the mashes cannot be used as a general quality criterion. Their data provide strong evidence that the preference biter almond lavour of spirits or the spirit, without this lavour, will remain a mater of personal taste.…”
Section: Distillation -Innovative Applications and Modelingmentioning
confidence: 99%
“…After oxidation to cyanate, it reacts with ethanol to form ethyl carbamate (Aresta et al 2001;Battaglia et al 1990;MacKenzie et al 1990;Taki et al 1992;Wucherpfennig et al 1987). Because of the fact that the concentration of ethyl carbamate varies over a broad range in stone-fruit spirits, a light-and time-dependent formation after distillation and storage can be assumed (Andrey 1987;Baumann and Zimmerli 1988;Lachenmeier et al 2005;Mildau et al 1987;Schehl et al 2005;Suzuki et al 2001;Zimmerli and Schlatter 1991).…”
Section: Ethyl Carbamate (Urethane)mentioning
confidence: 99%
“…This is currently accomplished by using selected and well-characterised existing commercial yeast strains with low urea excretion during fermentation (Butzke and Bisson, 1997). Each specific food processing application nevertheless needs a specific optimization step and the use of specific strains in specific conditions (Schehl et al, 2005). Another possibility is to use urease enzyme to limit urea level.…”
Section: Preventing Actions and Related Environmental Issuesmentioning
confidence: 99%